Hubungan Kebiasaan Digendong Dengan Kemampuan Berguling Pada Bayi Usia 20 Minggu - Turyati, Sri; , Agus Widodo, S.Fis.,Ftr., M.Fis; , Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes (2015)
Background: Carrying habitual toward the 0 till 20 weeks old baby is the condition where the baby position is in front with the stretch position, feet straight also head support with arm or put into carry so baby's motorist system development will be limited the movement of the baby especially rolling habitual. Purpose: To know that there is a relation about carrying habitual with rolling ability toward baby and to know there is a relation between the frequency and carrying time with carrying ability. The benefit of the research: Can be known the relation of carrying habitual with rolling ability toward 20 weeks old baby. Research method: This research is observational research with cross sectional research design. The sampling technique use simple random sampling with the inclusion and exclusion criteria. The carrying habitual measurement use questioner and the rolling ability use cross motor function measure. The statistic analysis use chi-square. The result of the research: From statistic analysis find out that the result of carrying habitual out of the standard value not significant is affected the rolling ability(p= 0,347 > 0,005), carrying frequency out of standard significant is affected rolling ability(p=0,211 > 0,005), and the duration out of standard value is not significant affected rolling ability(p=0,961 > 0,005). Conclusion: statically carrying habitual not significant to affect rolling ability. The frequency is not significant to affect rolling ability. The duration is not significant to affect rolling ability. Key words: carrying habitual, carry, carrying frequency, carrying duration, rolling ability.